HOM and LOM coupler optimizations for the ILC crab cavity - Xiao, L; Ko, K; Li, Z; Ng, C; Schussman, G; Seryi, A; Uplenchwar, R; Burt, G; Goudket, P; McIntosh, P; Bellantoni, L (2007)
The FNAL 9-cell 3.9 GHz deflecting cavity designed for the CKM experiment was chosen as the baseline design for the ILC BDS crab cavity. Effective damping is required for the lower-order TM010 modes (LOM), the same-order TM110 π-mode (SOM) as well as the higher-order modes (HOM) to minimize the beam loading and beam centroid steering due to wakefields. Simulation results of the original CKM design using the eigensolver Omega3P showed that both the notch filters of the HOM/LOM couplers are too sensitive to the notch gap, and the damping of the SOM is insufficient for the ILC. To meet the ILC requirements, the couplers were redesigned to improve the damping and tuning sensitivity. With the new design, the damping of the LOM/SOM/HOM modes is significantly improved, the sensitivity of the notch filter for the HOM coupler is reduced by one order of magnitude and mechanically feasible, and the LOM coupler is simplified by aligning it on the same plane as the SOM coupler and by eliminating the notch filter. In this paper, we will present the coupler optimization, tolerance studies and multipacting analysis for the crab cavity. ©2007 IEEE.